Tadakhul al-Lughah al-Indunīsiyyah fī Mahārat al Kitābah Ladā at-Talāmīdz bi Ma’hadi al-‘Izzah al Islamiy al-‘Alamiy Batu - Fairuz Afra Yuslizar; Uril Bahruddin (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
Language interference is a common phenomenon among second-language learners and represents one of the major challenges in the language acquisition process. Since every language has its own linguistic system and grammatical rules, differences between the learners’ first language and the target language frequently lead to interference. In the context of Arabic language learning, many Indonesian students unconsciously apply the grammatical patterns of Indonesian when producing written Arabic texts, resulting in various linguistic errors. This study aims to identify the forms of Indonesian language interference in the Arabic writing of students at Al-Izza International Islamic Institute, Batu, and to examine the factors contributing to this phenomenon. The research employed a qualitative field study approach. Data were analyzed using Corder’s error analysis framework, which consists of data collection, error classification, error identification, error description and analysis, interpretation of interference, and error correction. The findings reveal that Indonesian language interference occurs at the grammatical, morphological, and semantic levels of students’ Arabic writing. These forms of interference are influenced by both internal factors, such as students’ linguistic competence and learning habits, and external factors, including instructional practices and the surrounding language environment. The study concludes that understanding the patterns and causes of language interference is essential for developing more effective instructional strategies that can improve students’ Arabic writing proficiency and minimize first-language influence.